(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article analyzes methodological approaches to developing the industrial machinery sector through green investments. It explores systemic, functional, sustainable development, and innovative approaches to enhance the environmental efficiency of industrial enterprises. Modern tools such as Life Cycle Assessment (LCA), Sustainable Return on Investment (S-ROI), and Multi-Criteria Decision Analysis (MCDA) are applied in a combined framework. The article also highlights digital transformation processes supported by IoT and Big Data technologies. Empirical and theoretical analysis methods are integrated to develop strategies based on real-world data. An interdisciplinary approach ensures the integration of economic, environmental, and social criteria. Emphasis is placed on forming a competitive and sustainable industrial machinery model through green investment. The proposed methodological model can serve as a practical basis for policy-making and investment projects.